RETROSPECTIVE AUDIT OF PATIENTS TREATED FOR MDR-TB IN RE-TREATMENT CATEGORY - Saeed, Waseem; Naseem, Arshad; Ahmed, Jamal (Journal of Ayub Medical College Abbottabad, 2009)
Objective: To determine the efficacy of our modified anti-tuberculosis regimen in adult patients with multi-drug-resistant tuberculosis (MDR-TB) in the re-treatment category. Methods: Retrospective chart review of 176 patients in re-treatment category with diagnosis of MDR-TB from 1st Jan 1993 to 31st Dec 2002 managed at the Department of Pulmonology Military Hospital Rawalpindi, Pakistan. All the patients were given four standard first line anti-TB drugs along with any two second line drugs out of Ofloxacin/Ciprofloxacin/Levofloxacin, Amikacin, or Clarithromycin and treatment was modified after availability of drug susceptibility testing (DST). Results: Seventy-two percent of the patients were young men with mean age of 32.28±8.7 yrs, 53.4% had moderately advanced while nearly 30% had extensive disease. One-third cases had contact with a patient of pulmonary tuberculosis out of which one fifth had contact with a MDR-TB patient. Mean duration of diagnosis of tuberculosis before therapy was 41.11±14.32 months and 70% of the cases had received at least 2 prior anti-TB regimens. They had received a median of four anti-TB drugs in past and were infected with organisms that were resistant to a median of 3 first line anti-TB drugs. Resistance to Ethambutol and PZA was about 18% and 11% respectively. A median of six anti-TB drugs was used while mean duration of therapy was 22.17±2.17 months. Bacteriological cure was achieved in about 90% cases while radiological response was documented in nearly 78%. Conclusion: Modified initial management strategy followed by DST guided therapy has yielded excellent results and needs to be assessed in further trials for wider application. Keywords: Modified regimen, Re-treatment TB, Multi-drug-resistant tuberculosis, MDR-TB, Tuberculosis